2023
DOI: 10.25165/j.ijabe.20231602.8003
|View full text |Cite
|
Sign up to set email alerts
|

Fluid-solid drag models selection for simulating wheat straw particle movement in anaerobic digester

Abstract: Computational fluid dynamics (CFD) has been utilized to simulate the movements of wheat straw particles for agitator speed selection in full-scale wet digestion. Previous research has found that the current drag model generally used for depicting the motion of spherical particles cannot match the movement behavior of wheat straw particles with their nonspherical shape. In this study, the sedimentation experiment and horizontal flow experiment of straw particles were determined using a V20-3D camera and a micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Different studies have also shown that the AD operation stage of biogas engineering is the most severe stage of GHG emissions and environmental pollution throughout the entire life cycle [63] . The addition of the nutrient urea further enhances the proportion of AD units in CSBP, which is similar to Lan's research results [64] . Lan found that the nutrient production part in the AD stage has the most serious environmental impact over the whole life cycle.…”
Section: Environmental Impact Potential Analysissupporting
confidence: 89%
“…Different studies have also shown that the AD operation stage of biogas engineering is the most severe stage of GHG emissions and environmental pollution throughout the entire life cycle [63] . The addition of the nutrient urea further enhances the proportion of AD units in CSBP, which is similar to Lan's research results [64] . Lan found that the nutrient production part in the AD stage has the most serious environmental impact over the whole life cycle.…”
Section: Environmental Impact Potential Analysissupporting
confidence: 89%